Pendidikan Informal sebagai Upaya Pelestarian Perkawinan Endogami (Studi Kasus di Desa Adat Tenganan Pegringsingan, Bali) - Ni Nyoman Putri Nursanti; Wilodati Wilodati; Siti Komariah (Universitas Pendidikan Mandalika, 2023)
This study aims to describe informal education as an effort to preserve endogamous marriages in the Tenganan Pegringsingan Traditional Village Bali. This study used a case study method with a qualitative approach. The subjects of this study were the heads (Kliang) of the Tenganan Pegringsingan Traditional Village, community leaders, and the natives of Tenganan (krama desa). Data were collected through observation, interview, and documentation. Meanwhile, the data analysis technique was interactive analysis through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicated that efforts to preserve endogamous marriage in the Traditional Village of Tenganan Pegringsingan Bali, could be done by implementing informal education reflected in the materuna nyoman and madaha rituals. This effort is meant for guiding children who are about to embark on adolescence so that they understand ethics, customs, norms, manners, system of governance, traditional village areas, and ceremonies held in the Tenganan Pegringsingan Traditional Village, and so that they are ready to move on to the next stages of life: adolescence, adulthood, and then marriage. Through these rituals, children were prepared to become village krama (natives of Tenganan), responsible for maintaining and following the traditional village's rules from an early age. Therefore, this process is expected to form a strong mentality so that the younger generation can preserve their key local wisdom, namely endogamous marriage.